Knowledge assessment of snake antivenom among healthcare practitioners involving educational intervention in northern Nigeria: a study protocol. (August 2020) - Bala, Auwal A.; Jatau, A.I.; Yunusa, Ismaeel; Mohammed, M; Mohammed, Al-Kassim H.; Isa, Abubakar M.; Wada, A.S.; Gulma, Kabiru A.; Bello, Inuwa; Michael, Godpower C.; Malami, Sani; Chedi, Basheer Z. A.
Introduction: Snakebite envenoming (SBE) is an important occupational and public health hazard especially in sub-Saharan Africa. For optimum management of SBE, adequate knowledge of Snake antivenom (SAV) is very critical among the healthcare practioners in this region. Information related to the knowledge of SAV use in the management of SBE, as well as SAV logistics is scarce among the Health Care Professionals (HCPs) in Nigeria, particularly in the northern region. We therefore aimed to develop, validate and utilize a tool to assess the SAV knowlegde among HCPs in northern Nigeria. We also sought to implement and evaluate an intervention that could improve the SAV knowledge among the HCPs. Methods: The proposed study will be conducted in three phases: Phase I will involve the development of the item-pool to be included in the tool, followed by a face, content validity and construct validity. The tool reliability, readability and difficulty index will be determined. Phase II will involve the utilization of the tool to assess baseline SAV knowledge among the HCPs followed by an educational intervention. Multiple Linear Regression analysis will be used to determine the factors associated with SAV knowledge among the HCPs. Lastly, Phase III which will be a repeat of Phase II to assess and evaluate the knowledge after the intervention. Discussion: The study design and findings may guide future implementation and streamline the intervention of improving SAV knowledge in HCPs training and practice. Lay Summary: Knowledge assessment and educational intervention of snake antivenom among healthcare practitioners in northern Nigeria: a study protocol Snakebite envenoming (SBE) is an important occupational and public health hazard especially in sub-Saharan Africa. For optimum management of SBE, adequate knowledge of snake antivenom (SAV) is very critical among the healthcare practitioners. The baseline knowledge SAV dosage, mode of administration, availability, and logistics is very relevant among healthcare professionals, particularly those that are directly involved in its logistics. It is paramount that SAV is handled and used appropriately. The efforts and advocacy for the availability for more SAV will be in vain if not handled appropriately before they are used. This study protocol aims to develop a tool, to assess SAV knowledge and effects of educational interventions among healthcare professionals (HCPs) in northern Nigeria. This protocol suggests conducting studies in three phases: (a) Development and validation of SAV knowledge assessment tool, (b) Baseline assessment of SAV knowledge assessment tool among HCPs, and (c) Development, implementation and evaluation of an educational intervention to improve SAV knowledge among HCPs in northern Nigeria.